Patient-centered Outcomes in Breast Cancer: Description of EQ-5D-5L and EORTC-QLQ-BR23 Measurements in Real-world Data and Their Association With Survival. Issue 9 (September 2022) - Monteiro, M.R.; Nunes, N.C.C.; Crespo, J.; Abrahão, A.B.K.; Buscacio, G.; Lerner, L.C.C.; Sermoud, L.; Arakelian, R.; Piotto, G.; Lemos, C.; Campos, R.; Victorino, D.; et al.
Abstract: Aims: In recent years, major improvements in breast cancer treatments have led to a significant increase in survival. Despite that, this population's quality of life (QoL) information is lacking, especially real-world data. Materials and methods: This was a prospective, multicentre, observational study of female breast cancer patients, without prior systemic treatment, treated between 2012 and 2019 in private health care in Brazil. QoL was assessed by two questionnaires, the EQ-5D-5L and the EORTC-QLQ-BR23. Additional data were retrospectively collected. Results: The study comprised 1372 patients, most with early-stage disease (80.2% stages 0–II). At a median follow-up of 25.6 months, the estimated 3-year overall survival was 93.6%. Patients with locally advanced and metastatic breast cancer had the lowest visual analogue scale scores and the highest symptom burden in all dimensions of EQ-5D-5L, but with the most significant improvement after treatment. With the EORTC-QLQ-BR23 questionnaire, patients undergoing lumpectomy had a better perception of body image. Axillary dissection led to greater arm symptoms after 12 months, radiotherapy enhanced breast symptoms and patients treated with chemotherapy had significant worsening in the effects of systemic therapy compared with endocrine or HER2 therapy. Staging and immunohistochemical subtype correlated with survival and with several QoL parameters, but overall survival was not independently affected by patient-reported outcomes in this cohort. Conclusion: Our results show that early diagnosis and access to treatments with fewer side-effects, such as endocrine or targeted therapy, and less aggressive surgeries are the best strategies to achieve a better QoL for breast cancer patients. Highlights: Real-world patient-reported outcomes are promising tools for patient-centered care. Advanced breast cancer leads to high symptom burden and worse perception of health. Patients undergoing lumpectomy had a better perception of body image. Adding radiation therapy to surgery increases symptoms in the breast. Chemotherapy is the systemic treatment that most reduces quality of life.